Ethnomathematics Exploration in Modulo Learning in Bekles Ball Games - Triayuni Hartati; Ellis Mardiana Panggabean (Indonesian Journal of Education and Mathematical Science, 2023)
The purpose of this research is to explore the relationship between Modulo Learning and the traditional game of bekles ball. The Bekles Ball Game is a traditional game which is a cultural heritage that is increasingly being played by today's generation of children. In order to keep the Bekles Ball Game maintained and not forgotten, there is one way that can be done, namely by applying it to the learning in the classroom so that this is the aim of this research. The Bekles Ball game is in fact related to Modulo Learning. This study used qualitative research with 2 informants from Class X-TKJ at SMK Nusantara Lubuk Pakam. The data collected is from the results of observations, interviews and in the form of documentation. In this study, the concept of division was used in Modulo 10 and Modulo 8. Based on this research, it can be seen that there is an ethnomathematics value in the bekles ball game which refers to learning the concepts of Modulo 10 and Modulo 8. It can be concluded that there are many ethnomathematics changes that we can do that can be used to learning media as an exploration of ethnomathematics.